Listeria monocytogenes: Strain Heterogeneity, Methods, and Challenges of Subtyping. Issue 12 (20th November 2015) - Nyarko, Esmond B.; Donnelly, Catherine W.
Abstract: Listeria monocytogenes is a food‐borne bacterial pathogen that is associated with 20% to 30% case fatality rate. L. monocytogenes is a genetically heterogeneous species, with a small fraction of strains (serotypes 1/2a, 1/2b, 4b) implicated in human listeriosis. Monitoring and source tracking of L. monocytogenes involve the use of subtyping methods, with the performance of genetic‐based methods found to be superior to phenotypic‐based ones. Various methods have been used to subtype L. monocytogenes isolates, with the pulsed‐field gel electrophoresis (PFGE) being the gold standard. Although PFGE has had a massive impact on food safety through the establishment of the PulseNet, there is no doubt that whole genome sequence (WGS) typing is accurate, has a discriminatory power superior to any known method, and allows genome‐wide differences between strains to be quantified through the comparison of nucleotide sequences. This review focuses on the different techniques that have been used to type L. monocytogenes strains, their performance challenges, and the tremendous impact WGS typing could have on the food safety landscape.